Human‐directed social behaviour in dogs shows significant heritability. (24th March 2015) - Persson, M. E.; Roth, L. S. V.; Johnsson, M.; Wright, D.; Jensen, P.
Abstract : Through domestication and co‐evolution with humans, dogs have developed abilities to attract human attention, e.g. in a manner of seeking assistance when faced with a problem solving task. The aims of this study were to investigate within breed variation in human‐directed contact seeking in dogs and to estimate its genetic basis. To do this, 498 research beagles, bred and kept under standardized conditions, were tested in an unsolvable problem task. Contact seeking behaviours recorded included both eye contact and physical interactions. Behavioural data was summarized through a principal component analysis, resulting in four components: test interactions, social interactions, eye contact and physical contact. Females scored significantly higher on social interactions and physical contact and age had an effect on eye contact scores. Narrow sense heritabilities (h 2 ) of the two largest components were estimated at 0.32 and 0.23 but were not significant for the last two components. These results show that within the studied dog population, behavioural variation in human‐directed social behaviours was sex dependent and that the utilization of eye contact seeking increased with age and experience. Hence, heritability estimates indicate a significant genetic contribution to the variation found in human‐directed social interactions, suggesting that social skills in dogs have a genetic basis, but can also be shaped and enhanced through individual experiences. This research gives the opportunity to further investigate the genetics behind dogs' social skills, which could also play a significant part into research on human social disorders such as autism. Abstract : During a problem solving task, females beagle dogs displayed more human‐directed contact seeking behaviours than males